2021
DOI: 10.3390/healthcare9020185
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cigarette Smoking and Physical Fitness Level of Korean Adults and the Elderly

Abstract: Although previous studies have examined the relationship between smoking and physical fitness, they only considered current smoking status and the same fitness measurements regardless of age. This study investigated differences in physical fitness based on tobacco smoking habits. A total of 2830 non-elderly adults (NEA; 19–64 years) and 629 elderly (65–89 years) participated in the study, using data extracted from a Korean national database. One-way ANCOVA and ANOVA were conducted to analyze the results. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
13
1
3
Order By: Relevance
“…Kumar et al reported that nonsmoker athletes had higher flexibility than smokers ( 35 ). In contrast, previous studies found no differences in flexibility between smoking and nonsmoking men ( 20 , 36 ). In the present study, current smoker exhibited a lower performance in 3-min step, 1-min sit-up and sit-and-reach tests when compared with never smoker.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Kumar et al reported that nonsmoker athletes had higher flexibility than smokers ( 35 ). In contrast, previous studies found no differences in flexibility between smoking and nonsmoking men ( 20 , 36 ). In the present study, current smoker exhibited a lower performance in 3-min step, 1-min sit-up and sit-and-reach tests when compared with never smoker.…”
Section: Discussioncontrasting
confidence: 63%
“…Notably, a previous study suggested that abstinence from smoking may increase VO 2 max performance in males ( 28 ). Jeon et al ( 20 ) shown that quitting smoking were reverse the effects of smoking on the repetitions of 20-m shuttle run, but not on 50-m sprint, grip strength, 1-min sit-up and sit-and-reach tests in young adults. In the present study, we found that former smoker had the highest performance in 3-min step test among all groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though tobacco use has decreased in many high-income countries such as the United States and the United Kingdom, it is growing in many low- and middle-income countries [ 11 , 35 ]. According to the World Health Organization (WHO), there are more than 1.1 billion smokers throughout the world, with more than 80% of them residing in low- and middle-income countries [ 49 ]. After nonsurgical periodontal treatment, Varghese et al (2020) studied the salivary 8-hydroxyguanosine (8-OHdG) levels in smokers and nonsmokers with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Del mismo modo, los comportamientos de riesgo para la salud pueden impactar de manera negativa en el rendimiento físico. Por ejemplo, hallazgos anteriores han documentado que los niveles de rendimiento físico están asociados con el consumo de tabaco (Chaabane et al, 2016;Hashizume et al, 1999;Jeon et al, 2021), consumo de alcohol (Courtney et al, 2022) y pérdida de sueño (Fullagar et al, 2015;Sheikholeslami et al, 2018).…”
Section: Diseño Tipo De Investigación Y Participantesunclassified